2016
DOI: 10.1007/s11307-016-1024-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved Radiosynthesis and Biological Evaluations of L- and D-1-[18F]Fluoroethyl-Tryptophan for PET Imaging of IDO-Mediated Kynurenine Pathway of Tryptophan Metabolism

Abstract: We have developed a practical method for the automatic radiosynthesis of 1-L-[F]FETrp and 1-D-[F]FETrp. Our biological evaluation results suggest that 1-L-[F]FETrp is a promising radiotracer for PET imaging of IDO-mediated kynurenine pathway of tryptophan metabolism in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…Furthermore, the tryptophan analog, 1-D-methyl-tryptophan (1-D-MT) has proven to be superior to its L-counterpart and has been widely used in the clinic. Nevertheless, similar to previous findings in a breast cancer model 33,46 , our studies in Smo/Smo mice showed that the brain uptake of 1-D-[ 18 F]FETrp was very low as compared to that of its L-counterpart, possibly due to preference differences in the amino acid transporter. However, it should be noted that although the tumor uptake of 1-D-[ 18 F]FETrp in Smo/Smo mice was low, it was still slightly higher than that in the normal brain regions (contralateral cerebellum and cerebrum).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the tryptophan analog, 1-D-methyl-tryptophan (1-D-MT) has proven to be superior to its L-counterpart and has been widely used in the clinic. Nevertheless, similar to previous findings in a breast cancer model 33,46 , our studies in Smo/Smo mice showed that the brain uptake of 1-D-[ 18 F]FETrp was very low as compared to that of its L-counterpart, possibly due to preference differences in the amino acid transporter. However, it should be noted that although the tumor uptake of 1-D-[ 18 F]FETrp in Smo/Smo mice was low, it was still slightly higher than that in the normal brain regions (contralateral cerebellum and cerebrum).…”
Section: Discussionsupporting
confidence: 91%
“…It is common that the L-enantiomer of an amino acid PET tracer has higher tumor uptake than its D-counterpart 39,40 . Consistent with this, in breast cancer, it has previously been shown that L-and D-enantiomers of 1-[ 18 F]FETrp have different uptake profiles 33 . In these studies, the in vitro cell uptake in MDA-MB-231 cells and the in vivo tumor uptake in MDA-MB-231 mouse xenografts suggested that the uptake of 1-L-[ 18 F]FETrp is much higher than the D-counterpart.…”
Section: Specificity Of the 1-l-[ 18 F]fetrp Uptake In Medulloblastomsupporting
confidence: 71%
See 2 more Smart Citations
“…Recent developments for noninvasive in vivo metabolite imaging may provide a solution for this technical hurdle. 105,106 It should be noted, however, that systemic Trp levels can be affected by TDO, which is expressed in the liver constitutively and induced in some types of cancer, 42 suggesting that evaluation of this amino acid is not necessarily a sole reflection of IDO1 enzyme activity. Finally, understanding how IDO1 works in cancer cells, versus noncancer cells, in terms of the enzyme and signal transduction properties, is essential for targeting the full effects of this pleiotropic mediator of immune suppression.…”
Section: Ido1 Inhibitors In Cancer Immunotherapymentioning
confidence: 99%